A Complex Case with a Completely Percutaneous Solution: Treatment of a Severe Calcific Left Main in a Patient with Low-Flow Low-Gradient Aortic Stenosis - Bianchi, Renatomaria; Esposito, Giovanni Marco; Ciccarelli, Giovanni; Tartaglione, Donato; Golino, Paolo (Journal of Cardiology and Cardiovascular Medicine, 2024)
Background: This case study explores an integrated approach to managing a complex cardiac condition, presenting a comprehensive single-session intervention. This includes balloon valvuloplasty using a Nucleus 18 mm balloon, complex angioplasty with rotational atherectomy (rotablator) targeting calcified lesions in the left main and left anterior descending artery, and Transcatheter Aortic Valve Implantation (TAVI) with a 23 mm Sapien 3 valve, all performed on an 81-year-old woman. Furthermore, this report underscores the strategic left atrial appendage closure conducted three months post-procedure due to the patient’s elevated hemorrhagic risk. Case presentation: Facing critical coronary and valvular pathologies, the patient underwent a meticulously planned, single-session intervention. The process began with a balloon valvuloplasty using a Nucleus 18 mm balloon to address the aortic stenosis. This was followed by a high-risk angioplasty, during which the Impella CP device provided hemodynamic support and rotational atherectomy was employed to address the calcified coronary artery disease effectively. The same session saw the successful execution of TAVI using a 23 mm Sapien 3 valve. The comprehensive approach notably diminished procedural complications, illustrating the benefits of an integrated treatment pathway in managing high-risk patients. Three months later, the patient underwent a left atrial appendage closure, a critical move considering her high risk of hemorrhage. This procedure also provided an opportunity to assess the favorable outcomes of the previous angioplasty. Conclusion: This case validates the feasibility and efficacy of performing multiple advanced percutaneous interventions in a single session for high-risk cardiac patients. It underscores the crucial role of innovative and personalized treatment strategies in improving patient outcomes, particularly in complex clinical scenarios. Moreover, the case exemplifies the essential relationship between immediate, comprehensive intervention and subsequent follow-up procedures in ensuring optimal long-term patient care.